In memory of the sociologist M.Sc. Cecilia Arguedas Marín (1943-2019) - Revista de Ciencias Sociales, Equipo editorial (2020)
The Journal of Social Sciences of the University of Costa Rica dedicates this Special Section to the Magister Cecilia Arguedas Marín, who was its editor for almost four decades, who died in June 2019. Doña Cecilia is an example of dedication to intellectual activity, which she combined with social activism, faithful to his conception of sociology committed to improving the quality of life of subordinate groups, the search for equity and social justice.